Delayed Anaerobic Threshold in Heart Failure Patients With Atrial Fibrillation. Issue 3 (May 2016) - Palermo, Pietro; Magrì, Damiano; Sciomer, Susanna; Stefanini, Elisa; Agalbato, Cecilia; Compagnino, Elisa; Chircu, Cristina M.; Maffessanti, Francesco; Teodoru, Minodora; Agostoni, Piergiuseppe
Abstract : PURPOSE: To assess whether atrial fibrillation (AF) in heart failure (HF) affects oxygen uptake at anaerobic threshold ( O2 AT) and heart rate (HR) kinetics. METHODS: A total of 15 patients with HF and AF and 18 with HF and sinus rhythm (SR) performed a maximal incremental and 2 constant workload cycle ergometer cardiopulmonary exercise tests (below and above AT, at 25% and 75% of maximal workload, respectively). At constant workload tests, kinetics of O2 and HR were assessed by calculating time constant (τ). RESULTS: HF patients with AF showed a similar peak O2 to those with SR (16.7 ± 4.5 mL/kg/min vs 16.6 ± 3.9 mL/kg/min). However, O2 AT (11.3 ± 2.9 mL/kg/min vs 9.3 ± 2.8 mL/kg/min; P < .05), peak HR (149 ± 18.8 bpm vs 116.4 ± 20.4 bpm; P < .001), HR AT (125.3 ± 19.1 bpm vs 90.3 ± 15.5 bpm; P < .001), and HR increase during exercise were greater in HF patients with AF. Finally, τHR and τ O2 below and above AT were not significantly different. CONCLUSIONS: In HF patients with AF, despite a similar peak O2 compared with patients with HF and SR, O2 AT is higher because of a higher HR and a greater HR increase during exercise. One postulated mechanism would be a greater cardiac output increase at the beginning of exercise in HF patients with AF. The delayed AT generates uncertainty about the meaning of a O2 value at AT in HF patients with AF, because a higher AT is usually associated with better performance and a better prognosis. Abstract : We analyzed the influence of atrial fibrillation on oxygen uptake (O2 ) and heart rate in patients with heart failure, as evaluated by cardiopulmonary exercise testing. In atrial fibrillation, despite a similar peak O2, the O2 at anaerobic threshold was higher because of a greater heart rate increase during exercise.